2019
DOI: 10.3390/molecules24224088
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activities of Isogosferol, a Furanocoumarin Isolated from Citrus junos Seed Shells through Bioactivity-Guided Fractionation

Abstract: Citrus junos Tanaka is a traditional medicine for treating coughs, dyspepsia, diabetes, asthma, neuralgia, and inflammatory disorders, and is distributed in Asia, especially in Korea, Japan, and China. This study aimed to use bioactivity-guided fractionation to find therapeutic phytochemicals from C. junos seeds, which can attenuate inflammatory responses. Nine coumarins (1–9) were isolated from the methanolic extract of C. junos seed shells and the inhibitory effects against inflammatory mediators were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…senecioyloxyosthol (5) [8], psoralen (6), bergapten (7), isoimperatorin (8) [9], oxypeucedanin (9) [10], oxypeucedanin hydrate (10) [10,11], pranferol (11) [12], scopoletin (12), and scoparone (13) [13]; the fractionation of the dichloromethane extract of the root of N. papillaris yielded several novel osthol derivatives, i.e., 4′-hydroxyosthol (2), 4′-acetoxyosthol (3) and neopapillarine (4) ( Figure 1). In addition to their cytotoxic and anticancer activities [14,15], natural and semi-synthetic coumarins possess many biological activities properties [16] such as antiviral [17][18][19], antifungal, antioxidative [20,21], antibacterial [22] and anti-inflammatory activities [23]. It should be noted that aflatoxins, potent hepatotoxic, carcinogenic, mutagenic and teratogenic mycotoxins isolated from Aspergillus species, also contain a coumarin nucleus as part of their polycylic heterocyclic structure [24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…senecioyloxyosthol (5) [8], psoralen (6), bergapten (7), isoimperatorin (8) [9], oxypeucedanin (9) [10], oxypeucedanin hydrate (10) [10,11], pranferol (11) [12], scopoletin (12), and scoparone (13) [13]; the fractionation of the dichloromethane extract of the root of N. papillaris yielded several novel osthol derivatives, i.e., 4′-hydroxyosthol (2), 4′-acetoxyosthol (3) and neopapillarine (4) ( Figure 1). In addition to their cytotoxic and anticancer activities [14,15], natural and semi-synthetic coumarins possess many biological activities properties [16] such as antiviral [17][18][19], antifungal, antioxidative [20,21], antibacterial [22] and anti-inflammatory activities [23]. It should be noted that aflatoxins, potent hepatotoxic, carcinogenic, mutagenic and teratogenic mycotoxins isolated from Aspergillus species, also contain a coumarin nucleus as part of their polycylic heterocyclic structure [24].…”
Section: Resultsmentioning
confidence: 99%
“…2.55 ppm) indicating a molecular formula of C15H16O4 for 2 which that is in agreement with the hydoxylated isoprenyl side chain added to the osthol structure. Although this compound has previously been reported as a rat metabolite of osthol [25], both the 1 H-NMR and 13 C-NMR spectra In addition to their cytotoxic and anticancer activities [14,15], natural and semi-synthetic coumarins possess many biological activities properties [16] such as antiviral [17][18][19], antifungal, antioxidative [20,21], antibacterial [22] and anti-inflammatory activities [23]. It should be noted that aflatoxins, potent hepatotoxic, carcinogenic, mutagenic and teratogenic mycotoxins isolated from Aspergillus species, also contain a coumarin nucleus as part of their polycylic heterocyclic structure [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Membranes were then blocked with 5% skim milk power in platin buffer [4 M NaCl and 1 M Tris-HCl (PH 7.5)] for one hour at RT. Primary antibodies against iNOS, COX-2, NF-κB , ERK1/2, and pERK1/2 were incubated with the membrane for 24 h at 4 • C. Membranes were then washed with wash buffer (4 M NaCl, Tween-20, 1 M Tris-HCl (PH 7.5)) in DW and then incubated with a second antibody (1:2000 dilution) at RT for 2 h. Protein signals were detected with a bio image system (Microchemi 4.2 Chemilumineszenz-System, Neve Yamin, Israel) using ECL solution (Thermo Fisher Scientific, Waltham, MA, USA) [36].…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Previously, we identified extracts with anti-inflammatory activity and fractions of coumarins using Citrus junos seeds. Additionally, we also attempted to discover novel anti-inflammatory phytochemicals from extracts that contain limonoids as their bitter constituents [ 12 ]. It was reported that some limonoids, such as obacunone, a limonoid abundantly distributed in citrus fruits, have anti-inflammatory activities [ 13 ].…”
Section: Introductionmentioning
confidence: 99%